Análisis de las oportunidades del sector floricultor exportador colombiano frente a las actuales condiciones del mercado en Costa Rica (2018)
The opportunity analysis proposes to investigate the recent environment of the floriculture market in Costa Rica. There’s possibility that Colombian floriculture’s field obtains benefits of this new destiny as a business opportunity? To this is necessary get the right information about several points of the destiny country like the floriculture environment, socio – cultural environment, politics, economy and its geographic conditions.